The "oldest and coldest" shipped living donor kidneys transplanted through kidney paired donation. Issue 1 (20th August 2019) - Nassiri, Nima; Kwan, Lorna; Bolagani, Aswani; Thomas, Alvin G.; Sinacore, Joseph; Ronin, Matthew; Cooper, Matthew; Segev, Dorry L.; Cecka, J. Michael; Veale, Jeffrey L.
Abstract : To date, thousands of living donor kidneys have been shipped through kidney paired donation (KPD). To expand on this growing segment of living donor transplantation, we evaluated the effect of advanced age donation ("oldest kidneys") and prolonged cold ischemia time ("coldest kidneys") on graft function and survival using the National Kidney Registry database from February 2008 to May 2018. Donors were stratified by age at time of donation (<65 or ≥65 years) and kidneys were stratified by cold ischemia time (<16 or ≥16 hours). We evaluated delayed graft function and death‐censored graft failure (DCGF) for up to seven posttransplant years. Of the 2363 shipped living donor kidney transplants, 4.1% of donors were ≥65 years and 6.0% of transplanted kidneys had cold ischemia times ≥16 hours. Delayed graft function and DCGF occurred in 5.2% and 4.7% of cases. There were no significant associations between delayed graft function and donor age ( P = .947) or cold ischemia ( P = .532). Donor age and cold ischemia time were not predictive of delayed graft function (OR = 0.86, 1.20; P = .8, .6) or DCGF (HR = 1.38, 0.35, P = .5, .1). These findings may alleviate concerns surrounding the utilization of kidneys from older donors or those originating from distant transplant centers. Abstract : The authors evaluate the effect of advanced donor age and prolonged cold ischemia time on graft function and survival using the National Kidney Registry database and find that transplants from donors older than 65 years and cold ischemia times longer than 16 hours were not at a higher risk of developing delayed graft function or death‐censored graft failure.